PENGARUH KUALITAS LAYANAN, KUALITAS PRODUK DAN CITRA PERUSAHAAN TEHADAP KEPUASAN PELANGGAN ADVANCE DIGITAL - Aprillia, Fryda; Alimuddin Rizal (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine the effect of service quality, product quality and company image on Advance Digitals customer satisfaction. This study was conducted on Advance Digitals Semarang customers. This study uses a purposive sampling method with the criteria of people who have bought and used Advance Digitals Semarang products. The number of respondents who were determined for this study were 205 people. With the help of the SPSS statistical program version 25.0, it can be seen the relationship between variables using multiple linear regression analysis. The results obtained from this study indicate that, firstly, although the service quality and product quality variables have a positive regression coefficient value, this variable does not significantly affect customer satisfaction, and the corporate image variable has a positive and significant effect on customer satisfaction.